Analisis Kurangnya Pemanfaatan dan Upaya Konservasi Mangrove oleh Masyarakat di Kecamatan Pantai Labu - Sanas Tasia Sihaloho; Cahya Putri Ramadhani; Rosma Purba; Asima Tiara Agnesia Pasaribu; Meilinda Suriani Harefa (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Mangroves are plants whose natural habitat is in coastal areas, they should require the role of coastal communities to manage mangroves. In Pantai Labu District, four types of mangrove plants were found that grow abundantly in the area, namely mangroves (Rhizophora), api-api (Avicennia), nipah (Nypa), and pedada (Sonneratia caseolaris). Although the types of mangroves in this area are quite diverse, unfortunately the community has not utilized them optimally. So far, the community has only taken parts of the mangrove tree trunks to be used as firewood or sold, while the fruit, especially pedada fruit, is often left alone to rot without being utilized. The method in this study uses qualitative descriptive. This study aims to describe and understand the conditions of mangrove utilization and conservation efforts by the community in Pantai Labu District in depth, based on data obtained from observations and interviews with local residents.